Advanced Collagen‐Based Biomaterials for Regenerative Biomedicine. (26th November 2018) - Lin, Kaili; Zhang, Dawei; Macedo, Maria Helena; Cui, Wenguo; Sarmento, Bruno; Shen, Guofang
Abstract: In recent decades, collagen is one of the most versatile biomaterials used in biomedical applications, mostly due to its biomimetic and structural composition in the extracellular matrix (ECM). Several attempts are proposed for designing innovative collagen‐based biomaterials and applying them in tissue regeneration. The regeneration of different tissues is prompted by different types and diverse physical forms of collagen‐based biomaterials prepared by various methods. Based on such concepts, the source, structure, and classification of collagen are briefly introduced in this review. Here, the commonly used physical forms and modification methods of collagen‐based biomaterials are reviewed, including hydrogels, scaffolds, and microspheres, followed by their applications in the regeneration of tissues and organs. Important proof‐of‐concept examples are described to demonstrate the outcomes on material characteristics, cellular reactions, and tissue regeneration. A concise assessment of the limitations that still exist and the developing trends in the future of collagen‐based biomaterials are put forward. Abstract : In this review, an overview of the different physical forms of collagen‐based biomaterials is provided and the corresponding commonly used fabrication methods as well as advanced technologies in detail followed by examples of their applications in the regeneration of tissues and organs are discussed. The limitations and potential development directions are also listed at the end.